Guilt, suffering, and memory : Germany remembers its dead of World War II - Margalit, Gilʿad 1959-2014 (Indiana Univ. Press, 2010)
Coping with guilt: the Germans and the Nazi past -- Remembering national suffering in World War II -- German memory and remembrance of the dead from 1945 to the 1960s -- Memorial days in West Germany and their metamorphosis, 1945-2006 -- The bombing of Germany's cities and German memory politics, 1945-1989 -- Flight and expulsion in German political culture and memory since 1945 -- The resurgence of the German sense of victimization since reunification